Brain Dysfunction in LAMA2-Related Congenital Muscular Dystrophy: Lessons From Human Case Reports and Mouse Models - Arreguin, Andrea J.; Colognato, Holly (Frontiers in Molecular Neuroscience, 2020)
Laminin α2 gene (LAMA2)-related Congenital Muscular Dystrophy (CMD) was distinguished by a defining central nervous system (CNS) abnormality—aberrant white matter signals by MRI—when first described in the 1990s. In the past 25 years, researchers and clinicians have expanded our knowledge of brain involvement in LAMA2-related CMD, also known as Congenital Muscular Dystrophy Type 1A (MDC1A). Neurological changes in MDC1A can be structural, including lissencephaly and agyria, as well as functional, including epilepsy and intellectual disability. Mouse models of MDC1A include both spontaneous and targeted LAMA2 mutations and range from a partial loss of LAMA2 function (e.g., dy2J/dy2J), to a complete loss of LAMA2 expression (dy3K/dy3K). Diverse cellular and molecular changes have been reported in the brains of MDC1A mouse models, including blood-brain barrier dysfunction, altered neuro- and gliogenesis, changes in synaptic plasticity, and decreased myelination, providing mechanistic insight into potential neurological dysfunction in MDC1A. In this review article, we discuss selected studies that illustrate the potential scope and complexity of disturbances in brain development in MDC1A, and as well as highlight mechanistic insights that are emerging from mouse models.